Pengaruh Struktur Mikro terhadap Sifat Mekanik Material Logam - Baitul, Baitul Maharani lubis; Tika Gajah; Radit Atilasyah (JURNAL RISET RUMPUN ILMU TEKNIK, 2026)
The objective of this study is to comprehensively examine and analyze the influence of microstructure on the mechanical properties of metallic materials. Microstructure is known to play a crucial role in determining the mechanical behavior of metals; therefore, a thorough understanding of this relationship is essential for the development of engineering materials. This study adopts a systematic literature review approach, employing descriptive analysis and meta-analysis of recent scientific publications obtained from various reputable academic databases. The analysis results indicate that microstructure is a significant determinant of the mechanical characteristics of metallic materials, including strength, ductility, and resistance to deformation. The most influential microstructural parameters include grain size, phase distribution, crystallographic orientation, dislocation density, and the presence and characteristics of precipitates. Among these parameters, grain size has been shown to be the most dominant factor. The Hall–Petch strengthening mechanism demonstrates that grain refinement can increase the tensile strength of materials by approximately 200 to 300 percent. In addition, materials with multi-phase microstructures, such as dual-phase steels and TRIP steels, exhibit an excellent combination of strength and ductility compared to single-phase materials. Based on the meta-analysis results, each metallic material system exhibits a trade-off between strength and ductility, whereby an increase in strength is generally accompanied by a reduction in ductility. These findings indicate that achieving an optimal combination of mechanical properties for specific application requirements necessitates a comprehensive and integrated microstructural engineering approach.